New Perspectives on Power and Political Representation from Ancient History to the Present Day Repertoires of Representation - Kaal, Harm; Slootjes, Daniëlle (Radboud Studies in Humanities, 2019)
This volume examines modes of political communication between rulers and ruled from antiquity to the present by applying the concept of representation. It explores the dynamic relationship between elites and the people which is shaped by self-representation and representative claims. Readership: All scholars and students interested in the phenomenon of political representation, from antiquity to the present day.